PREVALENCE OF CERVICAL CANCER AMONG THE WOMEN’S ATTENDING THE TERTIARY CARE CENTER OF EASTERN PART OF BIHAR - kumar, binay; Prasad, Nidhi (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective of this study was to study the prevalence of cervical cancer and its grade in the patients presenting to the gynecology outpatient department (OPD) of a tertiary care center. Methods: This is a record based cross-section study which shows the percentage of women having pathological cervical lesions from the total number presenting to gynecology OPD of our tertiary hospital with specific symptoms with in a period of more than past 2 year. Results: As the catchment area is of lower status general health which was low and routine regular check-up was not considered important by the patients. Poor knowledge about cancer cervix and lack of regular screening at primary center’s was the main constraint. The mean age of patient was 37±5.4 years and shows that maximum incidence that is reported is of negative for intraepithelial lesion for malignancy followed atypical squamous cells of undetermined significance and high-grade squamous intraepithelial lesion. Discussion: The major limitation found in this study was lack of proper knowledge among patients, poor health-care facilities, and shortage of trained staffs. It is essential to upgrade the basic facilities of primary health-care centers and mass education to vulnerable age group and enhanced awareness on this issue will lead to early diagnosis and greater chance of screening leading to timely diagnosis and treatment. Conclusion: Lack of awareness has led to underreporting and faulty health seeking behaviour has led to delayed diagnosis. Comprehensive approach and affordable extended package of health care under Ayushmann Bharat can be helpful in reducing the disease burden.